A Cross Sectional Study on the Frequency of Poly-Arthropathy in HCV Positive Patients with Positive Ra Factor - Urooj Mehtab Raina, Arbab Nisar, Muhammad Kashif Bashir, Habib Ur Rehman, Shoaib Liaquat, Ahmad Raza, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The Aim Of This Study Was The Determination Of The Rheumatoid Factor (Rf) Frequency In Hepatitis C Infection (Hcv) Patients And Its Correlation With Poly-Arthropathy. Study Design: The Design Of This Study Was Cross-Sectional Study. This Study Was Conducted at Sheikh Zayed hospital Rahim yar khan, and the Duration Of This Study Was From October, 2020 To March, 2021. 207 Confirm Patients of Hepatitis C Infection With The Positive Hcv Rna And Anti-Hcv Antibodies Through Pcr Qualitative Having Poly-Arthropathy Were Made A Part Of The Research. The Rf Screening Of These Patients Was Carried Out Through Immune-Chromatography With The Help Of Rf Latex Assay Kit. Results: In The Total Sample Male To Female Ratio Was Respectively 138 Males (66.67%) And 69 Females (33.33%). Range Of The Age In The Patients Was In The Limit Of 21 – 55 Years With The Mean Age As (44.29 ± 4.61) Years. The Youngest Age Was 21; Whereas The Eldest Patient’s Age Was 55 Years In The Research Sample. Majority If The Sample Population Was In The Age Group Of 36 – 45 Years As 97 Patients (47%). The Rate Of Rf Positive Was Observed In The 88 Patients (42.51%) And Negative Incidence Was Observed In 119 Patients (57.49%) Being Affected By Hepatitis C Infection Related With The Poly-Arthropathy. Rf Frequency Of The Female Cases Was Observed As 66 Cases (48%) And In The Male Cases It Was Observed As 22 Patients (32%) With A Significant P-Value Observed As (0.0367), Which Was Dominant In Females In Comparison To The Male Cases. Conclusion: Rheumatoid Factor (Rf) Detection Is Of Less Use For The Diagnosis Of The Patients’ Coexisting Ra In The Cases Of Chronic Hcv Infection Due To An Increased Percentage Of The Rf Serum Activity.